Balance-Of-Plant Computerized Operator Support System Implementation. (December 2020) - Mortenson, Torrey; Ulrich, Thomas; Boring, Ronald Laurids; Lew, Roger
A Computerized Operator Support System (COSS) is an operator assistive technology suite that aids operators in monitoring processes to detect off-normal conditions, diagnose plant faults, predict future plant states, recommend mitigation alternatives, and select appropriate mitigative actions. A COSS human-machine interface (HMI) was developed at Idaho National Laboratory (INL) in collaboration with an advanced prognostics engine called PRO-AID, developed at Argonne National Laboratory (ANL). The front-end HMI coupled with the back-end prognostics provide fault prediction to inform operators of plant faults before they occur. Historically, COSS has been focused within the control room, representing systems that are monitored and controlled solely from a centralized location. This project, however, is focused on applying the principles of previous COSS efforts to a system outside the control room, namely the boric acid concentrator and liquid radwaste (BAC/LRW) system. This effort demonstrates the applicability and usability of a COSS system in a balance-of-plant environment, and offers next steps in the development of operator support and advanced overview interfaces in existing nuclear power-generating stations, and the future advanced reactor systems.